New dinosaur remains and the tetrapod fauna from the Upper Cretaceous of Mato Grosso State, central Brazil. (4th July 2018) - Sales, Marcos A. F.; Martinelli, Agustín G.; Francischini, Heitor; Rubert, Rogério R.; Marconato, Leonardo P.; Soares, Marina B.; Schultz, Cesar L.
Abstract: Mato Grosso State is the main area of paleontological investigations in central Brazil, especially regarding Upper Cretaceous beds. Fossil collection in the surroundings of the Morro do Cambambe started as early as late nineteenth century, but prospections and studies are still ongoing. This contribution presents new dinosaur specimens recovered from Upper Cretaceous outcrops of the southeastern portion of Mato Grosso State. These remains enabled the first report of a megaraptoran theropod based on a vertebral centrum and the description of abelisaurid (a fragmentary tooth) and titanosaur remains (a tooth and a fragment of a dorsal vertebra). Based on the amount of compiled reports of tetrapod remains from Mato Grosso, mainly from meeting abstracts and technical reports, the evidence at hand indicates a diverse Upper Cretaceous tetrapod assemblage still poorly explored in comparison to other Upper Cretaceous units of Brazil and Gondwana, in general.